2006
DOI: 10.1002/lsm.20362
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy and anti‐tumor immunity

Abstract: Preclinical studies have shown that local photodynamic therapy (PDT) enhances systemic antitumor immunity. In addition, it has long been known that the long-term efficacy of PDT depends on the presence of an intact adaptive immune system. Years of research in the laboratory have attempted to shed light on the mechanisms of the PDT-enhanced antitumor immune response, suggesting that increased expression of proinflammatory cytokines may play a key role. This overview on the immunologic potential of PDT briefly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
86
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 42 publications
3
86
0
3
Order By: Relevance
“…Thus it is possible that local PDT treatment of tumours leads to release of factors capable of bypassing the need for CD4 þ T cells in the activation of DCs. In support of this hypothesis, we have recently shown that PDT treatment of EMT6 and Colon26 tumours enhances maturation and activation of DCs and that DCs isolated from PDT treated mice are able to stimulate T-cell effector functions (Gollnick et al, 2006).…”
Section: à2mentioning
confidence: 77%
“…Thus it is possible that local PDT treatment of tumours leads to release of factors capable of bypassing the need for CD4 þ T cells in the activation of DCs. In support of this hypothesis, we have recently shown that PDT treatment of EMT6 and Colon26 tumours enhances maturation and activation of DCs and that DCs isolated from PDT treated mice are able to stimulate T-cell effector functions (Gollnick et al, 2006).…”
Section: à2mentioning
confidence: 77%
“…PDT generated inflammatory mediators together with components released from tumor cells can also activate antigen presenting cells capable of stimulating effector T-cell proliferation and cytokine secretion (11). Recently, Yokogawa et al (12) demonstrated that topical Imiquimod, a Toll-like receptor 7/8 agonist, could trigger T-cell infiltrates in SCCs.…”
Section: Introductionmentioning
confidence: 99%
“…The destruction of targeted lesions by PDT results from localised production of reactive oxygen species mediated by drugs (photosensitisers) capable of capturing the energy of light and transferring it to molecular oxygen (Henderson and Dougherty, 1992;Dougherty et al, 1998). Unlike immunologically silent genotoxic damage produced by radiotherapy and chemotherapy, photooxidative cytotoxic lesions generated by PDT are extranuclear and result in a rapid cell death that alerts host's immune surveillance elements (Castano et al, 2006;Gollnick et al, 2006;Korbelik, 2006). Hence, tumour PDT induces a strong host response mediated by innate immune system and characterised by overt inflammatory and acute phase responses that culminates in the acquirement of adaptive immunity recognising the treated tumour as its target (Korbelik, 2006).…”
mentioning
confidence: 99%